2005
DOI: 10.1038/sj.ejcn.1602119
|View full text |Cite
|
Sign up to set email alerts
|

Can children and adolescents use photographs of food to estimate portion sizes?

Abstract: Objective: The goals of this study were to investigate whether children and adolescents can accurately estimate portion sizes of preweighed food by viewing photographs of food, and whether age influences the ability to estimate food portion sizes. Subjects: A total of 63 male and female volunteers aged 9-19 y participated in the study. Design: Each participant received a photographic booklet with photograph series of 13 food items. Participants over 10 y of age were asked to estimate portion sizes of food on 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
7
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 14 publications
9
118
7
1
Order By: Relevance
“…No age-related differences in accuracy were reported in other studies (9,12,15) . No significant differences in accuracy or time were detected by gender, similar to other studies (17) .…”
Section: Discussioncontrasting
confidence: 52%
“…No age-related differences in accuracy were reported in other studies (9,12,15) . No significant differences in accuracy or time were detected by gender, similar to other studies (17) .…”
Section: Discussioncontrasting
confidence: 52%
“…In addition, its been found that consumers can be sceptical of food photographs when displayed on food packaging with the belief that they are for marketing purposes only (5) . In contrast, food photographs were found to be relatively accurate PSEA for use with children (28)(29)(30) . Nevertheless, there are no validated alternative PSEA for composite foods.…”
Section: Discussionmentioning
confidence: 74%
“…These studies, and numerous others not from South Asia (24)(25)(26)(27)(28)(29)(30)(31)(32)(33) , have reported bias (percentage error), percentage of correct photographs selected, ratios between estimated and weighed portions and/or correlations between weighed and recall methods. These are important measures for tools that are developed to aid the estimation of group-level mean nutrient intakes and risks of nutrient deficiency (5) .…”
mentioning
confidence: 88%